PENGARUH INFLASI, KURS, TINGKAT SUKU BUNGA, PERTUMBUHAN EKONOMI, DAN JUMLAH UANG BEREDAR TERHADAP JUMLAH DPK BANK SYARI’AH - YENTI AFRIDA; ROMI ISKANDAR (Maqdis: Jurnal Kajian Ekonomi Islam, 2018)
This study explores the influence of Inflation Rate, Exchange Rate, Interest Rate, Economy Growth, and Money Supply toward saving and deposit fund in Indonesian sharia Banking 2001 to 2015 period. Published time series data by Indonesian Central Bank (BI), Indonesian Financial Authority (OJK), Statistic Central Bureau (BPS) were used in this study. The empirical tests using a path analyses model to support the research hypotheses. The results show that inflation rate, exchange rate, interest rate, economy growth, and money supply in Indonesia influence toward sharia banking saving and deposit fund by positive and significant effect during this period.